The Outcome of Patients With Cystic Biliary Atresia With Intact Proximal Hepatic Ducts Following Hepatic-Cyst-Jejunostomy. Issue 2 (1st June 2022) - Asai, Akihiro; Wu, Jia-Feng; Wang, Kasper S.; Yamataka, Atsuyuki; Nio, Masaki; Su, Da-Jyun; Short, Celia; Tsuboi, Koichi; Ochi, Takanori; Sasaki, Hideyuki; Okubo, Ryuji; Yodoshi, Toshifumi; et al.
Abstract : Objectives: To determine the outcomes of patients with cystic biliary atresia by correlating the anatomy of the hepatic ducts with the choice of biliary reconstruction surgery. Background: The Kasai hepatoportoenterostomy (Kasai) is the initial surgical procedure offered to most patients with biliary atresia. In contrast, a hepatic-cyst-jejunostomy has been reported to be effective in patients with the cystic form of biliary atresia. Methods and Results: We performed an international multicenter retrospective review. Two hundred eighty-seven patients were included, and 33 cases of cystic biliary atresia were identified. Outcomes were the serum total bilirubin level 3 months post-surgery and native liver survival at 2 years of age and were compared between cases who received the Kasai versus hepatic-cyst-jejunostomy in correlation to the anatomy of proximal hepatic ducts. The patients were categorized into 3 anatomical groups: patent intact hepatic ducts (n = 10), patent hypoplastic hepatic ducts (n = 13), and obliterated hepatic ducts (n = 10). All 10 patients with patent intact hepatic duct group underwent hepatic-cyst-jejunostomy, and 9 experienced bile drainage and native liver survival. Among the 13 patients with hypoplastic hepatic ducts, 11 underwent the Kasai procedure, and 9 had bile drainage, whereas 2 underwent hepatic-cyst-jejunostomy, and one survived with the native liver. All of the patients with obliterated hepatic ducts underwent the Kasai procedure; 5 established biliary drainage and survived with the native liver. Of 5 who did not drain, 3 underwent liver transplantation. Conclusions: In patients with cystic biliary atresia, the subset with a connection between cyst and intrahepatic bile ducts via intact proximal hepatic ducts had favorable clinical outcomes following hepatic-cyst-jejunostomy.